MODIFIKASI RESIN Ca-ALGINAT DENGAN ABU JERAMI PADI SEBAGAI MATERIAL PENGISI KOLOM PADA TAHAPAN PRAKONSENTRASI ANALISA ION Mn (II) SECARA OFF- LINE - Adhi Surya Pranata Surya Pranata; Bohari Yusuf; Aman Sentosa Panggabean (JURNAL KIMIA MULAWARMAN, 2014)
The modification of resin Ca - Alginate with rice straw ash as a column filler material for preconcentration step of Mn(II) ion. Has been done Preconcentration method was used by off-line method, water samples were passed through the column and eluted with 0.1 M H2SO4. The eluate was taken and detected by using Spectrophotometer UV-Visible. Optimum composition of modified resin Rice straw ash - Ca - Alginat were at 1% Na - Alginate, 0.1 M CaCl2, and 0.5 g rice straw ash. The result of research shown the optimum condition of retention capacity ion Mn(II) was 0.08211 mg Mn / gr resin. The best sorption at pH 2, and optimum condition of eluent concentration 0.1 M H2SO4, sample volume 12 mL and eluent volume was 5 mL. The analytical performance of this method was good for determination of ion Mn(II) that could be evaluated by limit of detection about 0.7727 mg/L with the reproducibility level shown by the precentage of the coefficient variance was 1.179 %. This method could be applicated to determine ion Mn(II) at the natural water samples from Mahakam river with a recovery percentage of > 95 %, used spike method that shown this resin is good to using at preconcentration stage determination of ion Mn(II).